2015
DOI: 10.1080/00222895.2015.1090389
|View full text |Cite
|
Sign up to set email alerts
|

Critical Index of Difficulty for Different Body Motions: A Review

Abstract: K.-C. Gan and E. R. Hoffmann (1988) demonstrated that there is a clear boundary between values of Fitts' index of difficulty (ID) below which movements may be made without ongoing path corrections; above this value it was necessary to use corrections to hit a target of high ID. It is shown that this critical ID (IDcrit) value is dependent on both the body component making the movement and on the form of feedback available to the person. The arm system, having the highest ratio of muscle strength to mass moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Previous studies reported that the does not strongly influence the endpoint distribution [8,25,63]. For these typical pointing tasks, participants perform closed-loop motions [20]. In contrast, the endpoint distribution for when participants perform a ballistic motion has been reported to be affected by [20,38,46,61].…”
Section: Generalizability Of Success-rate Prediction Model To On-scrementioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies reported that the does not strongly influence the endpoint distribution [8,25,63]. For these typical pointing tasks, participants perform closed-loop motions [20]. In contrast, the endpoint distribution for when participants perform a ballistic motion has been reported to be affected by [20,38,46,61].…”
Section: Generalizability Of Success-rate Prediction Model To On-scrementioning
confidence: 91%
“…For these typical pointing tasks, participants perform closed-loop motions [20]. In contrast, the endpoint distribution for when participants perform a ballistic motion has been reported to be affected by [20,38,46,61]. Beggs et al [6,7] formulated the relationship in this way:…”
Section: Generalizability Of Success-rate Prediction Model To On-scrementioning
confidence: 99%
See 3 more Smart Citations